Teaching French at Higher Education and Curriculumn Issues: Mengajar Bahasa Prancis di Pendidikan Tinggi dan Masalah Kurikulum - Ortikovna, Sattorova Marifat (Universitas Muhammadiyah Sidoarjo, 2022)
This article aims to evaluate the effects resulted from the implementation of a new curriculum for the teaching of French as a foreign language (FFL) at undergraduate level. Since majority of students found foreign language coursebooks (FLCs) not motivating, a curriculum that aims to develop language competences by excluding FLCs was designed. The theoretical framework of the curriculum is based on the Common European Framework of Reference for Languages, on the Bologna Process and on the National Qualifications Framework for Higher Education. The designed curriculum may be used in different institutions if altered in line with learners’ needs.